Multi-omic Characterization of Intraspecies Variation in Laboratory and Natural Environments - Megan G. Behringer (American Society for Microbiology, 2021)
Investigation of microbial communities has led to many advances in our understanding of ecosystem function, whether that ecosystem is a subglacial lake or the human gut. Within these communities, much emphasis has been placed on interspecific variation and between-species relationships.